Effects of Interruptions on Consumer Online Decision Processes - Xia, Lan; Sudharshan, D. (Journal of Consumer Psychology, 2002)
The growth of e‐commerce and its attendant new technology features has increased interactivity in consumer information processing and decision‐making processes. The pull and push of information can be both more personalized and more commonly used. The ease of pushing information may lead to interruptions in consumer information processing that are more pronounced than those experienced in non‐Internet environments. Our study investigated the impact of interruption frequency, timing, and content and the moderating effects of consumer knowledge, control, and goal type on time spent on the decision task as well as satisfaction with the decision process and the choice. Our results show that the right configuration of interruptions may lead to increased online viewing time, whereas ill‐designed interruptions may be detrimental.